Preserved T-cell response in anti-CD20-treated multiple sclerosis patients following SARS-CoV-2 vaccination. (December 2022) - Faissner, Simon; Heitmann, Neele; Rohling, Ricarda; Ceylan, Ulas; Bongert, Marielena; Plaza-Sirvent, Carlos; Marheinecke, Corinna; Pedreiturria, Xiomara; Ayzenberg, Ilya; Hellwig, Kerstin; Schmitz, Ingo; Pfaender, Stephanie; et al.
Background: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has tremendous implications for the management of patients with autoimmune conditions such as multiple sclerosis (MS) under immune therapies targeting CD20 + B cells (aCD20). Objectives: Here, we investigated humoral and cellular immune responses, including anti-spike titers, neutralization against SARS-CoV-2 wild-type (WT), delta, and omicron variant and T cell responses of aCD20-treated relapsing–remitting MS patients following SARS-CoV-2 vaccination compared with healthy controls. Methods: Blood samples were collected within 4–8 weeks following the second vaccination against SARS-CoV-2. Sera were analyzed for anti-SARS-CoV-2 spike antibodies and neutralization capacity against pseudovirus for wild-type (WT), delta, and omicron variant. Peripheral blood mononuclear cells (PBMCs) were stimulated with a SARS-CoV-2 peptide pool and analyzed via flow cytometry. Results: The aCD20-treated MS patients had lower anti-SARS-CoV-2-spike titers, which correlated with B cell repopulation. Sera of aCD20-treated patients had reduced capacity to neutralize WT, delta, and omicron pseudoviruses in vitro . On the contrary, PBMCs of aCD20-treated patients elicited higher frequencies of CD3 + T cells and CD4 + T cells and comparable response of cytotoxic T cells, while Th1 response was reduced following restimulation with SARS-CoV-2. Conclusion: In summary, aCD20-treated patients have a reduced humoral immune response, depending on B cell repopulation, in accordance with preserved cellular immune response, suggesting partial cellular protection against SARS-CoV-2.